2010
DOI: 10.1002/jnr.22505
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the p75NTR signaling pathway in persistent synaptic suppression coupled with synapse elimination following repeated long‐term depression induction

Abstract: Synaptic plasticity, especially structural plasticity, is thought to be a basis for long-lasting memory. We previously reported that, in rat hippocampus slice cultures, repeated induction of long-term depression (LTD) by application of a metabotropic glutamate receptor (mGluR) agonist led to slowly developing, long-lasting synaptic suppression coupled with synapse elimination. We referred to this phenomenon as LOSS (LTD-repetition-operated synaptic suppression) to discriminate it from conventional single LTD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The role of the hippocampus in extinction has also been demonstrated by Barnes et al (2008) who have shown that inhibition of proBDNF cleavage in the CA1 region facilitates extinction (Barnes and Thomas, 2008). ProBDNF signaling via the p75 receptor facilitates long-term depression which could underlie the extinction process (Egashira et al, 2010). In this regard, it is worth noting that we observed in adult BDNF HET rats levels of proBDNF in the hippocampus that were comparable to WT levels.…”
Section: Fear Conditioning/extinction -Learning and Memorysupporting
confidence: 55%
“…The role of the hippocampus in extinction has also been demonstrated by Barnes et al (2008) who have shown that inhibition of proBDNF cleavage in the CA1 region facilitates extinction (Barnes and Thomas, 2008). ProBDNF signaling via the p75 receptor facilitates long-term depression which could underlie the extinction process (Egashira et al, 2010). In this regard, it is worth noting that we observed in adult BDNF HET rats levels of proBDNF in the hippocampus that were comparable to WT levels.…”
Section: Fear Conditioning/extinction -Learning and Memorysupporting
confidence: 55%
“…For example, p75NTR-deficient mice have a higher spine density than wild-type mice, and conversely, p75NTR overexpression in wild-type neurons decreases spine density (15). A high affinity ligand for p75NTR, pro-BDNF, eliminates dendritic spines via p75NTR (16). In this study, we showed that BDNF decreased dendritic spine density when CSPGs were added and that this effect was attenuated by neutralization by anti-p75NTR antibody (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…TrkB promotes dendritic spine formation (10), p75NTR, another BDNF receptor, mediates spine elimination (15,16). Thus, we investigated whether p75NTR is involved in decreased spine formation elicited by CSPGs in BDNF-treated neurons.…”
Section: Involvement Of P75ntr In Effects Of Cspgs On Spine Formationmentioning
confidence: 99%
“…In fact, altered expression of AMPA receptor subunits is observed in the hippocampus of p75 NTR knockout mice (61). Second, p75 NTR acts as a negative regulator of dendritic spine density and morphology (24,75). Accordingly, KI mutant mice show a significant loss of dendritic spines in CA1 pyramidal neurons, a phenotype recovered by normalization of p75 NTR levels, suggesting that synaptic and memory deficits in HD could be related to a reduction in the number and complexity of hippocampal dendritic spines.…”
Section: Discussionmentioning
confidence: 99%